Valuation of CO2 Emissions Reduction from Renewable Energy and Energy Efficiency Projects in Africa: A Case Study of Burkina Faso - Rice Verouska Nono Seutche; Marie Sawadogo; Firmin Nkamleu Ngassam (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
Burkina Faso like many other African countries hosts many renewable energy (RE) and energy efficiency (EE) projects that are not registered to the clean development mechanism (CDM), but which could represent potential CDM opportunities. This study seeks to determine these projects’ impact on the level of CO2 emissions in the country, and to determine their CDM potential by quantifying their carbon emissions reduction, using approved CDM methodologies adapted to the projects. 21 RE projects and 7 EE projects were considered, and all proven to be additional. Results revealed that, 68709.424 MWh and 9430.446MWh were saved and displaced by the EE and RE projects respectively annually, accounting for 48157.668 tCO2e emissions reduced annually. This accounts for a 63.12% emissions reduction from the baseline scenario and represents a huge potential for the CDM, ready to be harnessed. The total amount of emissions reduced could generate about 48157.668 Certified Emissions Reduction (CERs) yearly. Considering a carbon price of 10/tCO2e and a 10-year fixed crediting period starting from 2020 would imply a total revenue of 4815766.8 in 2030 from the CERs , which will increase the sector’s attractiveness to investors. Policies promoting the registration of these projects to the CDM are essential to boost the development of more of such projects in the country/ region, which will benefit from the sustainable development the CDM offers, while contributing to the achievement of its Intended Nationally Determined Contributions.